Asam amino rantai cabang terhadap status gizi, dan perubahan metabolik pada penyakit hati: Sebuah tinjauan sistematis - Wityadarda, Carissa; Immanuella, Ester Hanantika; Ndopo, Fernando Diaz; Ester, Teresa; Siregar, Sarah Damayanti; Berliana, Yuli (Poltekkes Kemenkes Aceh, 2025)
Background: Liver diseases such as non-alcoholic fatty liver disease (NAFLD) and cirrhosis are influenced by factors like viral infections, alcohol, immune dysfunction, genetic predisposition, and metabolic factors. Branched-chain amino acids (BCAAs)—leucine, isoleucine, and valine—are vital for protein metabolism and liver function. The role of BCAAs in liver disease and metabolic changes requires further study.Objectives: To evaluate the role of BCAAs in nutritional status and metabolic changes in liver disease through a systematic review.Methods: A systematic review was conducted following the PRISMA protocol. Literature was searched on Google Scholar for publications from 2019 to 2024. Studies were selected based on inclusion and exclusion criteria. Descriptive analysis summarized the findings, and statistical tests evaluated the relationship between BCAA consumption or supplementation and liver disease progression.Results: Eight studies met the inclusion criteria. High BCAA consumption was associated with an increased risk of NAFLD (OR = 1,32, p < 0,001). In contrast, BCAA supplementation improved MELD and CP scores in cirrhotic patients. Elevated BCAA levels were also linked to a higher risk of type 2 diabetes (OR = 1,60, 95% CI = 1,14-2,23, p = 0,006).Conclusions: BCAA supplementation may help slow cirrhosis progression and improve sarcopenia and liver function. However, its use should be tailored to avoid adverse effects. More research is needed to explore long-term effects on liver disease.